ChemInform Abstract: Convenient Stereoselective Synthesis of β‐Perfluoroalkyl α, β‐Unsaturated Esters via Horner—Wadsworth—Emmons Reactions. Issue 3 (29th December 2015) - Yamazaki, Takashi; Mano, Noriko; Hikage, Reo; Kaneko, Tsutomu; Kawasaki‐Takasuka, Tomoko; Yamada, Shigeyuki
Abstract: Various title esters are obtained with high (E)‐stereoselectivity by condensation reactions of in situ produced halogenated ketones with Horner—Wadsworth—Emmons reagents.